Plan du port de Louisbourg avec ses fortifications. (William L. Clements Library Image Bank, 1730)
Relief shown pictorially and by hachures.; Colored, pen and ink plan of Louisbourg, with the harbor and adjacent shoreline.; Includes table of reference to military and natural features.; Also includes fortifications, overlapping lines of fire, cod flakes along the shore with names of settlers.; Scale in toises.